A Bioactive Extract Rich in Triterpenic Acid and Polyphenols from Olea Europaea Promotes Systemic Immunity and Protects Atlantic Salmon Smolts Against Furunculosis - Reyes-Lopez, F; Vallejos-Vidal, E (Frontiers Media S.A., 2021)
In the present study, the modulation of the transcriptional immune response (microarray analysis) in the head kidney (HK) of the anadromous fish Atlantic salmon (Salmo salar) fed a diet supplemented with an olive fruit extract (AQUOLIVE®) was evaluated. At the end of the trial (133 days), in order to investigate the immunomodulatory properties of the phytogenic tested against a bacterial infection, an in vivo challenge with Aeromonas salmonicida was performed. A total number of 1,027 differentially expressed genes (DEGs) (805 up- and 222 downregulated) were found when comparing the transcriptomic profiling of the HK from fish fed the control and AQUOLIVE® diets. The HK transcripteractome revealed an expression profile that mainly favored biological processes related to immunity. Particularly, the signaling of i-kappa B kinase/NF-kappa and the activation of leukocytes, such as granulocytes and neutrophils degranulation, were suggested to be the primary actors of the innate immune response promoted by the tested functional feed additive in the HK. Moreover, the bacterial challenge with A. salmonicida that lasted 12 days showed that the cumulative survival was higher in fish fed the AQUOLIVE® diet (96.9 ± 6.4%) than the control group (60.7 ± 13.5%). These results indicate that the dietary supplementation of AQUOLIVE® at the level of 0.15% enhanced the systemic immune response and reduced the A. salmonicida cumulative mortality in Atlantic salmon smolts. Copyright © 2021 Salomón, Furones, Reyes-López, Tort, Firmino, Esteban, Espinosa Ruíz, Quintela, Pinilla-Rosas, Vallejos-Vidal and Gisbert.